Boat noise impacts Lusitanian toadfish breeding males and reproductive outcome - Amorim, Maria Clara P (2022)
Anthropogenic noise is a growing threat to marine organisms, including fish. Yet very few studies have addressed the impact of anthropogenic noise on fish reproduction, especially in situ. In this study, we investigated the impacts of boat noise exposure in the reproductive success of wild Lusitanian toadfish (Halobatrachus didactylus), a species that relies on advertisement calls for mate attraction, using behavioural, physiological and reproductive endpoints. Two sets of artificial nests were deployed in the Tagus estuary and exposed to either ambient sound or boat noise during their breeding season. Toadfish males spontaneously used these nests to breed. We inspected nests for occupation and the presence of eggs in six spring low tides (in two years) and assessed male vocal activity and stress responses. Boat noise did not affect nest occupation by males but impacted reproductive success by decreasing the likelihood of receiving eggs, decreasing the number of live eggs and increasing the number of dead eggs, compared to control males. Treatment males also showed depressed vocal activity and slightly higher cortisol levels. The assessment of oxidative stress and energy metabolism-related biomarkers revealed no oxidative damage in noise exposed males despite having lower antioxidant responses and pointed towards a decrease in the activity levels of energy metabolism-related biomarkers. These results suggest that males exposed to boat noise depressed their metabolism and their activity (such as parental care and mate attraction) to cope with an acoustic stressor, consistent with a freezing defensive response/behaviour. Together, our study demonstrates that boat noise has severe impacts on reproductive fitness in Lusitanian toadfish. We argue that, at least fishes that cannot easily avoid noise sources due to their dependence on specific spawning sites, may incur in significant direct fitness costs due to chronic noise exposure.